Kinetic Studies of Heavy Metal Ion Sorption by Modified Oil Palm Waste Material - Naimah, Ibrahim; Azlinda, Abdul Ghani; Ragunathan, Santiagoo; Umi Fazara, Md. Ali; Nazerry Rosmady, Rahmat (Universiti Malaysia Perlis (UniMAP), 2008)
Organized by Universiti Malaysia Perlis (UniMAP), 9th - 12th June 2007 at Park Royal Hotel, Penang.